Clinicopathologic Comparison of High-Dose-Rate Endorectal Brachytherapy versus Conventional Chemoradiotherapy in the Neoadjuvant Setting for Resectable Stages II and III Low Rectal Cancer. (8th July 2012) - Smith, Jessica A.; Wild, Aaron T.; Singhi, Aatur; Raman, Siva P.; Qiu, Haoming; Kumar, Rachit; Hacker-Prietz, Amy; Hruban, Ralph H.; Kamel, Ihab R.; Efron, Jonathan; Wick, Elizabeth C.; Azad, Nilofer S.; et al.
Abstract : Purpose . To assess for differences in clinical, radiologic, and pathologic outcomes between patients with stage II-III rectal adenocarcinoma treated neoadjuvantly with conventional external beam radiotherapy (3D conformal radiotherapy (3DRT) or intensity-modulated radiotherapy (IMRT)) versus high-dose-rate endorectal brachytherapy (EBT). Methods . Patients undergoing neoadjuvant EBT received 4 consecutive daily 6.5 Gy fractions without chemotherapy, while those undergoing 3DRT or IMRT received 28 daily 1.8 Gy fractions with concurrent 5-fluorouracil. Data was collected prospectively for 7 EBT patients and retrospectively for 25 historical 3DRT/IMRT controls. Results . Time to surgery was less for EBT compared to 3DRT and IMRT (P < 0.001 ). There was a trend towards higher rate of pathologic CR for EBT (P = 0.06 ). Rates of margin and lymph node positivity at resection were similar for all groups. Acute toxicity was less for EBT compared to 3DRT and IMRT (P = 0.025 ). Overall and progression-free survival were noninferior for EBT. On MRI, EBT achieved similar complete response rate and reduction in tumor volume as 3DRT and IMRT. Histopathologic comparison showed that EBT resulted in more localized treatment effects and fewer serosal adhesions. Conclusions . EBT offers several practical benefits over conventional radiotherapy techniques and appears to be at least as effective against low rectal cancer as measured by short-term outcomes.